Tranexamic Acid for the Prevention of Blood Loss After Vaginal Delivery. Issue 1 (January 2019) - Sentilhes, Loïc; Winer, Norbert; Azria, Elie; Sénat, Marie-Victoire; Le Ray, Camille; Vardon, Delphine; Perrotin, Franck; Desbrière, Raoul; Fuchs, Florent; Kayem, Gilles; Ducarme, Guillaume; Doret-Dion, Muriel; et al.
Abstract : (Abstracted from N Engl J Med 2018;379:731–742) The use of tranexamic acid (TXA) reduces mortality in the setting of postpartum hemorrhage (PPH). This study investigated whether the prophylactic administration of TXA in addition to prophylactic oxytocin in women with vaginal delivery would decrease the incidence of PPH.